ESMCH: An Energy-Saving, Multi-Hop, Clustering, and Hierarchy Protocol for Homogeneous WSNs - Salman, Fadhil Mohammed; Mohammed, Ahssan Ahmmed; Joda, Fanar Ali (Iraqi Journal of Science, 2024)
The wireless sensor network (WSN) is one of the most important achievements of the modern technological revolution and greatly affects human life. These networks suffer from some limitations that affect their performance, such as the limited power of their devices. Clustering technology is one of the effective power conservation techniques that improves the performance of WSNs, so this article focuses on developing aggregation technology by proposing an Energy Saving, Multi-hops, Clustering, and Hierarchy (ESMCH) protocol for homogeneous WSNs. The proposed protocol improves clustering technology in several directions. The first direction is by determining the ideal number of cluster head nodes (CHs) suitable for the network, and the second is through the perfect choice of nodes that will represent CHs. The third trend is the selection of secondary CHs. The last trend is the formation of clusters, which depends on an important parameter (distance to CHs). The proposed system uses the TDMA method to schedule the data transfer process to CHs (inside the cluster) and the CSMA method to organize the exchange of data packets between CHs (outside the clusters) for delivery to the base station. The results of simulation experiments in MATLAB R (2020 a) show that the proposed protocol extends network lifetime by 32% compared to the LEACH algorithm and by 26% compared to the SEP algorithm. The results also display that the ESMCH protocol increased the throughput of the WSN by 16.8% compared to its throughput when using the SEP algorithm and by 30% when using the LEACH algorithm.